The Best Way to Realize a Dream is to Wake Up Malaysia at a crossroads: Can we make the transition? by Abdul Rahman Embong and Than Siew Yean (eds.), Bangi: Penerbit Universiti Kebangsaan Malaysia, 2011, 215 pp. - Heng Siam-Heng (Kajian Malaysia, 2011)
The book identifies the biggest challenge today in Malaysia's trajectory of development as the transformation of itself into a high income economy by 2020. The country has been stuck in the middle-income trap for the past 15 years, and the question is whether it is able to take the necessary leap to get out of it. It is a very timely study, especially in the context of advancing China, India, Brazil, Indonesia and Vietnam—all formidable contenders for global foreign direct investment (FDI). The challenge for Malaysia will be even more daunting.